Анализ работоспособности кабеля по данным ускоренных испытаний - Бугрименко, И. А.; Гардер, Сергей Евгеньевич; Корниль, Татьяна Леоновна (НТУ "ХПИ", 2012)
В статье рассмотрен метод, основанный на наблюдении прямых и косвенных прогнозных параметров технической системы в ходе ускоренных испытаний. Рассмотрена техническая система - электрокабель марки АВВГ 4х10. Определен остаточный ресурс и вероятность безотказной работы в конкретный момент времени эксплуатации.

The method of life remaining and unfailing work probability forecasting is considered in this article. It is based on observation of direct and indirect parameters of technical system during accelerated testing. It makes prediction about system state during the work in the normal conditions possible. As the example such technical system as power cable is taken. As the result, life remaining and unfailing work probability of taken system in some work time moment is presented.
Keywords: прогнозирование; эксплуатация; ресурс остаточный; электрокабель; диагностика